Jatropha curcas seed oil as new substrate for enzymatic methylhydroxylaminolysis. - Rafiee-Moghaddam, Roshanak; Salimon, Jumat; Haron, Md. Jelas; Jahangirian, Hossein (National Institute R and D of Materials Physics, 2013)
Synthesis of methyl fatty hydroxamic acids (MFHAs) was carried out using lipozyme RM IM based on Jatropha Curcas seed oil. Optimized conditions were obtained at a mole ratio of 6/1 of methyl hydroxylamine/oil, temperature at 41˚C, enzyme 30mg/mmol and 72 h of reaction time. At this optimal condition, the yield% of methyl fatty hydroxamic based on Jatropha Curcas seed oil was 93.92%. The product was characterized by Fourier transform infrared (FTIR), and proton and carbon nuclear magnetic resonance (¹H-NMR and ¹³C NMR) spectra.